In situ epoxidization of natural rubber latex by performic acid and the kinetics of the reaction - George B; Abraham S; Mathew N M (Indian Journal of Natural Rubber Research, 1992)
Epoxidation of natural rubber latex stabilised with a nonionic surfactant was carried out with performica acid generated in situ. The reaction was performed at 30, 45, 50 and 60 degree C at a dry rubber content (DRC) of 20 and concentration of formic acid and hydrogen peroxide 0.955 and 3.75 modle dm3 respectively in the aqueous phase of the latex. Product characterization by 1H NMR and IR spectroscopic methods indicated significant influence of temperature on the extent of epoxidation as well as ring opening reactions. Epoxidation to the extent of 25-35 mole per cent could be reached without ring opening. The concentration of ring opened products at higher levels of epoxidation was found to be low. The reaction followed pseudo-first order kinetics with the formation of performic acid as the rate dtermining step. This was further confirmed by carrying out the reaction at 10 and 15 per cent DRC keeping the formic acid and hydrogen peroxide concentrations in the aqueous phase the same.
Keywords: Epoxidization; Epoxidization kinetics; Natural rubber latex; Performic acid; Ring opening reactions